Quarta Colônia: um olhar sobre a “cultura” do arroz como identidade e patrimônio cultural de São João do Polêsine–RS - Bisognin, Roselaine de Oliveira (2022)
This study on the rice crop as the identity and cultural heritage of the municipality of São João do Polêsine — located in Quarta Colônia, Rio Grande do Sul State — provides a contextualization and an investigation into man’s action from the historical traces of time and space. Furthermore, it seeks to recover the value and relationship of the work of Italian immigrants and their descendants with the local/regional cultural tradition. In this sense, a survey was carried out by researching bibliographies and museum collections in the city and conducting interviews with people from the community. An explanatory research method was used to shed light on the theme and explain the results through a qualitative approach, providing meaning to the studied fact. This study contributes to reinterpreting the past and appreciating culture as elements that integrate the teaching-learning subjects, resulting in the proposal and construction of a book as the final product of this dissertation. This book records the history of rice cultivation and how this cereal, in addition to being an economic identity in the region, is part of its cultural heritage. The book was produced with the collaboration of third-, fourth-, and fifth-grade students of the La Salle and Pedro Paulo Pradella municipal elementary schools of São João do Polêsine to produce the illustrations. By using a method that works with the perspective of heritage education, the book in question was produced, which will enable, in the educational environment and in teaching-learning, contributions to reinterpret and appreciate the historical and cultural background of the place where the school is located. In other words, it will enable one to work on the school subjects through a teaching-learning process that fosters recognizing and appreciating cultural assets in a meaningful way in order to strengthen the local community’s sense of belonging from reflections on their cultural traditions, making them protagonists of their historical process.